Addressing incentive-driven prescribing - Zafar Mirza (Journal of the Pakistan Medical Association)
Market failures in health care1 thrive on conflict of interest. Take the example of market failure due to “information discrepancy” between doctors and patients. This uneven knowledge is the basis for exploitation by the alliance between the health technology industry and medical profession an alliance fraught with conflict of interest. Patients pay the cost through their health and money. Whereas market failures are well established and wellstudied phenomenon in health economics and health care literature, there is a weak research base, including in Pakistan, for conflict of interest in health care despite its characterization as “an invisible force shaping health systems and policies”.2 It “remain(s) a global issue that is neglected, underestimated, and overlooked by health policy makers and researchers”.